Valorization Of Paraffin Wastes Obtained From Plastic Pyrolysis By Catalytic Cracking - Herrera, José Ignacio Solís; Miranda, Barbara Cristina; Barquero, Alexander Davis; Rivera, German Jiménez (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this research it was studied the effect of the type of catalyst, the reaction temperature and the catalyst/paraffins weight ratio in the transformation of paraffins waste obtained from the pyrolysis of plastics by catalytic cracking. It was chosen the Zeolite Y and Zeolite ZSM-5 as catalysts, the catalyst/paraffin weight ratios of 0.4:1 and 0.20:1 and the reaction temperatures of 400˚C and 440˚C. The catalytic cracking reaction of the paraffins was carried out in a fixed bed reactor. By the statistical analysis it was determined that the type of catalyst has the most outstanding effect, thus with the Zeolite ZSM-5 an average yield of 27.43% was reached. In contrast, with the Zeolite Y was obtained a 13.10%. In addition, it was found that the yield increased by 1.2% when a temperature of 400 ° C was used compared to 440°C. The catalyst/paraffin weight ratio does not significantly affect the yield. According to the analyzes performed by gas chromatography to the liquid reaction products, it would be expected that through this process products like diesel, Jet A-1 aviation fuel and gasoline could be obtained.